Pengembangan Modul Bioteknologi Berbasis Potensi Lokal Cocos nucifera Di Kabupaten Batu-Bara Untuk Kelas XII SMA Negeri 1 Sei.Balai - Retno Dwi Septia Ningrum; Kartika Manalu; Riris Nurkholida Rambe (Universitas Cokroaminoto Palopo, 2022)
This study aims to produce a biotechnology module based on local potential Cocos nucifera that meets the criteria of being valid, practical and effective. This research includes research and development (Research and Development). This study uses the ADDIE development model with 5 stages, namely analysis (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). The subjects in this study were students in class XII of SMA Negeri 1 Sei.Balai with a total of 34 students. The instrument in this study used a questionnaire to see the validity and practicality of the learning media in the form of a module, while the test of student learning outcomes was in the form of pre-test and post-test to see the level of effectiveness of the developed module. The results of this study indicate that the validity level of the media expert validator is 85% and the validity level of the material expert validator is 88% with a very valid category. The practicality level of the learning module based on the biology teacher's response questionnaire is 97% and the practicality level based on the student response questionnaire is 91% with a very practical category. As for the effectiveness level based on the classical completeness of students at the pre-test stage of 19% with a very poor category, but at the post-test stage an increase of 85% with a good category, then the module based on local potential Cocos nucifera in this biotechnology material can said to be effective.